Bad to the Bone: The Role of the Insulin-Like Growth Factor Axis in Osseous Metastasis - Rieunier, Guillaume; Wu, Xiaoning; Macaulay, Valentine M; Lee, Adrian V; Weyer-Czernilofsky, Ulrike; Bogenrieder, Thomas (Clinical cancer research, 2019)
Bone metastases are a frequent complication of cancer that are associated with considerable morbidity. Current treatments may temporarily palliate the symptoms of bone metastases but often fail to delay their progression. Bones provide a permissive environment because they are characterized by dynamic turnover, secreting factors required for bone maintenance but also stimulating the establishment and growth of metastases. Insulin-like growth factors (IGF) are the most abundant growth factors in bone and are required for normal skeletal development and function. Via activation of the IGF-1 receptors (IGF-1R) and variant insulin receptors, IGFs promote cancer progression, aggressiveness, and treatment resistance. Of specific relevance to bone biology, IGFs contribute to the homing, dormancy, colonization, and expansion of bone metastases. Furthermore, preclinical evidence suggests that tumor cells can be primed to metastasize to bone by a high IGF-1 environment in the primary tumor, suggesting that bone metastases may reflect IGF dependency. Therapeutic targeting of the IGF axis may therefore provide an effective method for treating bone metastases. Indeed, anti-IGF-1R antibodies, IGF-1R tyrosine kinase inhibitors, and anti-IGF-1/2 antibodies have demonstrated antitumor activity in preclinical models of prostate and breast cancer metastases, either alone or in combination with other agents. Several studies suggest that such treatments can inhibit bone metastases without affecting growth of the primary tumor. Although previous trials of anti-IGF-1R drugs have generated negative results in unselected patients, these considerations suggest that future clinical trials of IGF-targeted agents may be warranted in patients with bone metastases.